Phosphonocarboxylates inhibit the second geranylgeranyl addition by Rab geranylgeranyl transferase - Baron, Rudi A. (2022)
Rab geranylgeranyl transferase (RGGT) catalyzes the posttranslational geranylgeranyl (GG) modification of (usually) two C-terminal cysteines in Rab GTPases. Here we studied the mechanism of the Rab geranylgeranylation reaction by bisphosphonate analogs in which one phosphonate group is replaced by a carboxylate (phosphonocarboxylate, PC). The phosphonocarboxylates used were 3-PEHPC, which was previously reported, and 2-hydroxy-3-imidazo[1,2-a]pyridin-3-yl-2-phosphonopropionic acid ((+)-3-IPEHPC), a >25-fold more potent related compound as measured by both IC50 and Ki. (+)-3-IPEHPC behaves as a mixed-type inhibitor with respect to GG pyrophosphate (GGPP) and an uncompetitive inhibitor with respect to Rab substrates. We propose that phosphonocarboxylates prevent only the second GG transfer onto Rabs based on the following evidence. First, geranylgeranylation of Rab proteins ending with a single cysteine motif such as CAAX, is not affected by the inhibitors, either in vitro or in vivo. Second, the addition of an -AAX sequence onto Rab-CC proteins protects the substrate from inhibition by the inhibitors. Third, we demonstrate directly that in the presence of (+)-3-IPEHPC, Rab-CC and RabCXC proteins are modified by only a single GG addition. The presence of (+)-3-IPEHPC resulted in a preference for the Rab N-terminal cysteine to be modified first, suggesting an order of cysteine geranylgeranylation in RGGT catalysis. Our results further suggest that the inhibitor binds to a site distinct from the GGPP-binding site on RGGT. We suggest that phosphonocarboxylate inhibitors bind to a GG-cysteine binding site adjacent to the active site, which is necessary to align the mono-GG-Rab for the second GG addition. These inhibitors may represent a novel therapeutic approach in Rab-mediated diseases.